The Impact of Mobile Learning on Physics Education: A Systematic Literature Review - Siswanto, Dwi Ambar Cahyaningtias; Iswanto, Bambang Heru; Rahmawati, Yuli (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
Mobile learning has become a significant medium in the educational landscape, especially with the increased usage of smartphones among students and educators. This Systematic Literature Review (SLR) aims to explore the impact of mobile learning on the transformation of physics education. This study obtained 50 out of 200 articles selected based on their relevance to the theme of mobile learning in physics education, citation metrics, and publication date between 2019 and 2024. The review highlights a significant increase in mobile learning research, with the rise occurring in 2020 due to the COVID-19 pandemic, which emphasized the growing potential of mobile learning for remote education. Mobile learning enhances the accessibility, engagement, and effectiveness of physics education by making the learning process more interactive, fostering student independence, and improving learning outcomes. The review also identifies improvements in students' critical thinking and problem-solving skills as key benefits of mobile learning in physics. However, it also highlights the necessity of regulations to prevent misuse and safeguard academic integrity. Practical recommendations for educators include integrating mobile learning with project-based approaches to improve conceptual understanding and student engagement in physics. This study suggests that mobile learning has a transformative role in physics education, opening up new avenues for innovation and further research.